Nudge theory and gambling: a scoping review - Fortier, Marie-Ève; Audette-Chapdelaine, Sophie; Auger, Anne-Marie; Brodeur, Magaly (Frontiers in Public Health, 2024)
Background: Gambling disorder (GD) is a pressing public health concern with significant societal costs. The recently developed nudge theory, which is rooted in behavioral economics, aims to influence the decision-making behaviors of individuals by implementing changes in the environment.Aim: This scoping review aims to synthesize the literature on nudge theory as it relates to gambling.: This scoping review accords with the Arksey and O'Malley framework, as refined by Levac et al. It includes only articles from peer-reviewed journals that focus, as main themes, on both nudge theory and gambling. The final study selection includes six articles.The scoping review process led to studies explaining how 1) nudges aim to prod people toward healthier gambling choices, fostering the adoption of more responsible gambling practices, and 2) some gambling features, called dark nudges (or sludges), exploit and harm the decisionmaking processes of people who gamble.This scoping review highlights the fact that many stakeholders are involved in the field of gambling, and that better cooperation between them would promote safer and more responsible gambling practices. Future research is also needed to empirically test nudges to develop a better understanding of their impact on those who gamble.